Energy efficiency : for engineers and technologists - Eastop, T. D. (Longman Scientific & Technical, 1990)
Summary: The subjects of this book are the technical and economic techniques and implications of improving the conversion and usage of energy. It studies the efficient use of energy set in a financial context, and is illustrated throughout with numerical worked examples and case studies.